2022
DOI: 10.7759/cureus.29253
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Platelet-Rich Plasma (PRP) and Local Corticosteroid Injection in Periarthritis Shoulder: A Prospective, Randomized, Open, Blinded End-Point (PROBE) Study

Abstract: BackgroundPeriarthritis or frozen shoulder, also called adhesive capsulitis, is characterized by stiffness and pain along with gradual loss of active and passive movement in the glenohumeral joint. More than 2-5% of the population suffers from periarthritis with a higher incidence in the age group of 40-60 years. The various treatment modalities used for its management include simple physiotherapy, short-wave therapy, ultrasonic therapy, transcutaneous electrical nerve stimulation, hydrotherapy, analgesics, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The proportion of comorbidities, such as diabetes and hypertension, was insignificant between the groups. Diabetes mellitus (38%) was the most common comorbidity in the study population, followed by hypertension (15%), which is consistent with the findings of Gupta et al [6].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The proportion of comorbidities, such as diabetes and hypertension, was insignificant between the groups. Diabetes mellitus (38%) was the most common comorbidity in the study population, followed by hypertension (15%), which is consistent with the findings of Gupta et al [6].…”
Section: Discussionsupporting
confidence: 92%
“…Aslani et al [18] also reported similar findings to our study, demonstrating improvements in QuickDASH score, reduction in shoulder pain, and improvement in ROM when assessing the role of PRP in managing FS. Ünlü et al [19] evaluated the efficacy of IA PRP injection versus normal saline in managing FS and found improvements in SPADI score and reductions in VAS score, similar to our results obtained in the PRP group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Research in recent years shows a large amount of data on the successful use of platelet-rich plasma, not only in experimental, but also in clinical medicine [1,4,6,8,9,16,19,20].…”
Section: Results Discussionmentioning
confidence: 99%